Association of catheter ablation for atrial fibrillation with mortality and stroke: A systematic review and meta-analysis. (1st September 2018) - Barra, Sérgio; Baran, Jakub; Narayanan, Kumar; Boveda, Serge; Fynn, Simon; Heck, Patrick; Grace, Andrew; Agarwal, Sharad; Primo, João; Marijon, Eloi; Providência, Rui
Abstract: Background: Maintenance of sinus rhythm has been associated with lower mortality, but whether atrial fibrillation (AF) ablation per se benefits hard outcomes such as mortality and stroke is still debated. Objective: To determine whether AF ablation is associated with a reduction in all-cause mortality and stroke compared with medical therapy alone. Methods: Literature search looking for both randomized and observational studies comparing AF catheter ablation vs. medical management. Data pooled using random-effects. Risk ratios (RR) with 95% confidence intervals (CI) used as a measure of treatment effect. The primary and secondary outcomes were all-cause mortality and occurrence of cerebrovascular events during follow-up, respectively. Results: Thirty studies were eligible for inclusion, comprising 78, 966 patients (25, 129 receiving AF ablation and 53, 837 on medical treatment) and 233, 990 patient-years of follow-up. The pooled data of studies revealed that ablation was associated with lower risk of all-cause mortality: 5.7% vs. 17.9%; RR = 0.44, 95% CI 0.32–0.62, p  < 0.001. In a sensitivity analysis by study design, a survival benefit of AF ablation was seen in randomized studies, with no heterogeneity (mortality risk 4.2% vs. 8.9%; RR = 0.55, 95% CI 0.39–0.79, p  = 0.001, I 2  = 0%), and also in observational studies, but with marked heterogeneity (6.1% vs. 18.3%; RR = 0.39, 95% CI 0.26–0.59, p  < 0.001, I 2  = 95%). The mortality benefit in randomized studies was mainly driven by trials performed in patients with left ventricular (LV) dysfunction and heart failure. The pooled risk of a cerebrovascular event was lower in patients receiving AF ablation (2.3% vs. 5.5%; RR = 0.57, 95% CI 0.46–0.70, p  < 0.001, I 2  = 62%), but no difference was seen in randomized trials (2.2% vs. 2.1%; RR = 0.94, 95% CI 0.46–1.94, p  = 0.87, I 2  = 0%). Conclusions: Ablation of atrial fibrillation associates with a survival benefit compared with medical treatment alone, although evidence is restricted to the setting of heart failure and LV systolic dysfunction. Highlights: Catheter ablation of AF may reduce mortality compared with medical treatment alone. Data does not lend unequivocal support to the theory of stroke reduction with ablation. Mortality and stroke rates in real - world patients significantly exceed those seen in randomized studies.